The Role of Dectin-1 Signaling in Altering Tumor Immune Microenvironment in the Context of Aging - Bhaskaran, Natarajan; Jayaraman, Sangeetha; Quigley, Cheriese; Mamileti, Prerna; Ghannoum, Mahmoud; Weinberg, Aaron; Thuener, Jason; Pan, Quintin; Pandiyan, Pushpa (Frontiers in Oncology, 2021)
An increased accumulation of immune-dysfunction-associated CD4+Foxp3+ regulatory T cells (Tregs) is observed in aging oral mucosa during infection. Here we studied the function of Tregs during oral cancer development in aging mucosa. First, we found heightened proportions of Tregs and myeloid-derived suppressor cells (MDSC) accumulating in mouse and human oral squamous cell carcinoma (OSCC) tissues. Using the mouse 4-Nitroquinoline 1-oxide(4-NQO) oral carcinogenesis model, we found that tongues of aged mice displayed increased propensity for epithelial cell dysplasia, hyperplasia, and accelerated OSCC development, which coincided with significantly increased abundance of IL-1β, Tregs, and MDSC in tongues. Partial depletion of Tregs reduced tumor burden. Moreover, fungal abundance and dectin-1 signaling were elevated in aged mice suggesting a potential role for dectin-1 in modulating immune environment and tumor development. Confirming this tenet, dectin-1 deficient mice showed diminished IL-1β, reduced infiltration of Tregs and MDSC in the tongues, as well as slower progression and reduced severity of tumor burden. Taken together, these data identify an important role of dectin-1 signaling in establishing the intra-tumoral immunosuppressive milieu and promoting OSCC tumorigenesis in the context of aging.